2016
DOI: 10.15561/20755279.2016.0604
|View full text |Cite
|
Sign up to set email alerts
|

Modern methodic of power cardio training in students’ physical education

Abstract: Abstract.Purpose: significant increase of students' physical condition and health level at the account of application of modern power cardio training methodic. Material: 120 students (60 boys and 60 girls) participated in the research. The age of the tested was 19 years. The research took one year. We used methodic of power and functional impact on trainees' organism (HOT IRON). Such methodic is some systems of physical exercises with weights (mini-barbells), to be fulfilled under accompaniment of specially se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 23 publications
0
27
0
1
Order By: Relevance
“…-determined a substantial increase in the level of physical development and health of students through the use of modern methods of cardio-strength training [30,34,35]; -estimated the level of physical health and biological age of students according to their level of physical activity [19];…”
mentioning
confidence: 99%
“…-determined a substantial increase in the level of physical development and health of students through the use of modern methods of cardio-strength training [30,34,35]; -estimated the level of physical health and biological age of students according to their level of physical activity [19];…”
mentioning
confidence: 99%
“…It was found that more than 84.8% of boys and 81.1% of girls have average physical fitness level (satisfactory) [25,26].…”
mentioning
confidence: 99%
“…For achievement high results in motor activity it is necessary to have high level of specific coordination [16]. For training motor rhythm it is necessary to consider and use the following: − Didactic laws of motor actions' formation [25,37]; − Individual and group models of motor actions' construction [23,26]; − Modern technologies of education and training [22,31]; − Adequate forms of pedagogic control [27,30]; − Models of successfulness prediction [24,32]; − Correlation of anthropometric and functional indicators [21,33]; − Criteria of motor coordination structure [19,29,33]; − Psychological indicators of reaction to physical load [20,28] considering health level [35,36]. Specific for football coordination abilities are those, which ensure optimal control of specific motor tasks' fulfillment.…”
mentioning
confidence: 99%